The Effect Of Work Discipline and Work Stress On The Performance Of Administrative Employees of The General Bureau Of The Regional Secretariat Of West Java Province - Armiati, Mariska; Sofyandi, Rd. Herman (Syntax Literate, 2023)
Dependent Every company definitely wants all of its employees to be professional, disciplined and responsible. Therefore, employee performance can be interpreted as one of the most important things in a company to achieve goals. Achieving high labor productivity requires good work discipline from employees. In addition to work discipline, work stress can effect an employee’s ability to increase or decrease performance. The purpose of this study was to determine the effect of work discipline and work stress on employee performance and the Administrative Bureau of the Secretariat General of West Java Province. The method used is a quantitative method with a descriptive and verification approach. Data collection techniques using simple random sampling. Samples are taken randomly from the population without regard to the population. Validity, reliability analysis, classical acceptance test, multiple linear regresi analysis, f-test and t-test were used for data analysis. The results of things study indicate that work discipline has a positive and significant effect on employee performnace, while work stress has a positive and insignificant effect on employee performance.